2007
DOI: 10.1152/ajpgi.00136.2007
|View full text |Cite
|
Sign up to set email alerts
|

Opposite regulation of endothelial NO synthase by HSP90 and caveolin in liver and lungs of rats with hepatopulmonary syndrome

Abstract: The hepatopulmonary syndrome is a complication of cirrhosis that associates an overproduction of nitric oxide (NO) in lungs and a NO defect in the liver. Because endothelial NO synthase (eNOS) is regulated by caveolin that decreases and heat shock protein 90 (HSP90) that increases NO production, we hypothesized that an opposite regulation of eNOS by caveolin and HSP90 might explain the opposite NO production in both organs. Cirrhosis was induced by a chronic bile duct ligation (CBDL) performed 15, 30, and 60 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
1
3
0
1
Order By: Relevance
“…A recent study has shown that on the first day after portal vein ligation in rats, early upregulation of eNOS activity is an initial event leading to NO overproduction and vasodilatation (6). Similar opposite regulation of eNOS has been observed in the liver and lungs of cirrhotic rats with the hepatopulmonary syndrome (22). eNOS phosphorylation by Akt was shown to be a potential mechanism for the induction of eNOS activity.…”
Section: Discussionsupporting
confidence: 74%
“…A recent study has shown that on the first day after portal vein ligation in rats, early upregulation of eNOS activity is an initial event leading to NO overproduction and vasodilatation (6). Similar opposite regulation of eNOS has been observed in the liver and lungs of cirrhotic rats with the hepatopulmonary syndrome (22). eNOS phosphorylation by Akt was shown to be a potential mechanism for the induction of eNOS activity.…”
Section: Discussionsupporting
confidence: 74%
“…The increased release of nitric oxide in the pulmonary circulation is related to an increased expression and activity of two isoforms of nitric oxide synthase (NOS), the endothelial NOS (eNOS) and the inducible NOS (iNOS). [511][512][513][514][515][516] Meanwhile, BT and the BT-related endotoxaemia and pro-inflammatory response also contribute to the accumulation of macrophages in the pulmonary microvasculature. 517 Endothelial activation of fractalkine (CX3CL1), a chemokine, in the lung may favour the adherence of monocytes in the pulmonary microcirculation.…”
Section: Pathophysiologymentioning
confidence: 99%
“…In an elegant study, Frossard et al (9) showed an opposite regulation of eNOS by HSP90 since greater NO synthesis in the lungs was associated with elevated eNOS and HSP90 interaction, whereas the contrary effect was observed in liver homogenates, in which NO production was decreased. Thus lesser NO production in the liver was attributed to eNOS-HSP90 uncoupling together with enhanced association of eNOS to the caveolin.…”
Section: Discussionmentioning
confidence: 99%